ДИДАКТИК ВОСИТАЛАР ТИЗИМИДАГИ АХБОРОТ МАЖМУАСИ, МАСОФАДАН ЎҚИТИШ, ТЕЛЕВИДЕНИЕ, КОМПЬЮТЕР, ИНТЕРНЕТ ВА БОШҚА МАНБАЛАРДАН ФОЙДАЛАНИШ ТЕХНОЛОГИЯСИ, УЛАРНИНГ НАТИЖАЛАРИ - Умаров, Х.А.; Умарова, Ф.А.; Шарипова, Г. (SCIENCE and SOCIETY, 2017)
The article deals with the issues of attention to the youth that are not able to attend the educational establishment because of different reasons. It is emphasized the necessity to help them find their place in life in future and using the distance learning with television, with the purpose of achieving success in education.
Keywords: television; computer; Internet; telecommunication